PREVALENCE OF HYPERTENSION IN DIFFERENT AGE GROUPS. (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
Metabolic syndrome (MS), which is based on insulin resistance. This syndrome includes a number of risk factors (FR): arterial hypertension (AH), HTH, dyslipoproteidemia (DLP), obesity, hyperurekemia and other risk factors. It should be noted that in some studies, the number of components included in MS varies. However, hypertension, BMI, hyperlipidemia and hyperinsulinemia remain the main components of MS.